IFN-inducible human phospholipid scramblase 1 (PLSCR1) protein restricts HIV-1 infection by inhibiting membrane fusion - Yajie Liu; Pei Li; Yi-Min Zheng; Yuta Hikichi; Sherimay D. Ablan; Eric O. Freed; Shan-Lu Liu (Proceedings of the National Academy of Sciences, 2025)
Human phospholipid scramblase 1 (PLSCR1) is an interferon-stimulated gene (ISG) that inhibits viral infections through various mechanisms. Here, we identify PLSCR1 as a host restriction factor that inhibits HIV-1 entry by impairing membrane fusion mediated by the envelope glycoprotein (Env). Using multiple cell types including the human SupT1 T cell line and purified CD4 + T cells, we demonstrate that PLSCR1 inhibits the replication of HIV-1 with diverse tropisms and subtypes, as well as HIV-2 and SIV. Mechanistically, we find that PLSCR1 blocks viral entry and cell-to-cell transmission, in part by restricting HIV-1 virion–cell and cell–cell fusion without affecting CD4 or CXCR4 expression or virus binding to the cell surface. Collectively, these findings establish PLSCR1 as a broad-spectrum lentiviral restriction factor that acts at the membrane fusion stage, thereby expanding our understanding of ISG-mediated antiviral defense.